Evaluación de la capacidad de acogida a través de matrices de impacto/aptitud del área de influencia del embalse Topocoro en el municipio de Betulia, Santander (Colombia) (2021)
The area of ​​influence of the Topocoro reservoir, in the municipality of Betulia Santander, has undergone various changes in the model of occupation of the territory, due to changes and new expectations of land use in the sector, which went from agricultural to commercial and livestock uses. of services. That is why it is necessary to reformulate the model of occupation of the territory in this sector of the municipality, to achieve this it is necessary to update the reading of the territory through the methodology of reception capacity of the physical environment proposed by the authors Gómez Orea and Gómez Villarino in the book Territorial Planning, which consists of carrying out the diagnosis and territorial analysis in terms of vocation from the impact / suitability matrices of the soil. The diagnosis made from secondary information consigned in the current Territorial Ordering Scheme included the analysis of the main ecological structure, threat from mass movements, agrological classification of the soil, land cover and the location opportunities given by the distance to roads. and piers that will build, based on an AHP analysis, the environmental units of integration in which the impact and suitability of the activities that are planned could be evaluated, giving as result maps of aptitude and impact, which show the affinity of the activities evaluated with each environmental unit. The analysis of the result is that the environmental units with the greatest impacts correspond to the environmental protection areas identified in the main ecological structure.